TB treatment support strategies for children, adolescents, and young adults in a low-incidence setting - Verhage, A.R.; Hesseling, A.C.; Koppelman, G.H.; Kerstjens, H.A.M.; Akkerman, O.W. (IJTLD open, 2025)
BACKGROUND Globally, TB programmes should pay attention to the treatment support needs of children and adolescents (0-24 years) given the high disease burden and specific care requirements. We examine how health care workers in a low-incidence setting monitor and support TB treatment and TB preventive treatment (TPT) in this population. METHODS A quantitative web-based cross-sectional survey was conducted from 1 December 2023 to 31 January 2024 among Dutch health care workers routinely caring for persons (0-24 years) in community- and hospital-based TB services. RESULTS Ninety-three health care workers participated. The most common strategies to monitor TB treatment and TPT were 1) verbal questioning on adherence (100% vs. 99%) and 2) evaluating clinical response to TB treatment (91%). Additional strategies were always used for TB treatment, with a pill organiser being the preferred method, while 50% seldom used extra strategies for TPT. Digital support technologies were rarely used for TB treatment and TPT by 78% and 90% of respondents, respectively. CONCLUSION Dutch health care workers relied on traditional methods to support TB treatment adherence with limited use of digital technologies and greater focus on disease than infection. Further research is needed to assess whether these strategies meet young people's needs in TB care and improve outcomes.